(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
Аннотация. В данной статье усовершенствована технологии с целью повышения качества готовой продукции, выбрана оптимальный вес и конфигурация слитка. Рассчитано на прочность деталей узлов оборудования состояния (валка, станины и универсального шпинделя). Annotation. In this article, technologies were improved in order to improve the quality of the finished product, the optimal weight and configuration of the ingot was chosen. Calculated on the strength of the parts of the condition equipment units (roll, bed and universal spindle).